Mental Health and Wellbeing in Lithuanian Medical Students and Resident Doctors During COVID-19 Pandemic - Stanyte, Agne; Podlipskyte, Aurelija; Milasauskiene, Egle; Király, Orsolya; Demetrovics, Zsolt; Ambrasas, Laurynas; Burkauskas, Julius; Steibliene, Vesta (Frontiers in Psychiatry, 2022)
Background The coronavirus disease 2019 (COVID-19) pandemic has had a negative effect on mental health and subjective psychological wellbeing. One of the most affected population is medical students, reporting higher levels of depression, anxiety, sleep difficulties, and overall poorer wellbeing. However, the relationship between depression, anxiety, and sleep difficulties, and subjective psychological wellbeing has not been extensively researched in medical students in the context of COVID-19 pandemic. The aim of this study was to investigate the associations between depression, anxiety, and sleep quality, and subjective psychological wellbeing. Methods In total, 524 medical students and resident doctors (78.6% female, mean age 24 ± 3 years old) participated in an online survey between December 2020 and February 2021. Participants completed the WHO—Five Wellbeing Index Questionnaire, the Pittsburgh Sleep Quality Index questionnaire, the Patient Health Questionnaire-9, and the Generalized Anxiety Disorder Assessment-7. Results Multivariable logistic regression analysis showed that female participants’ worse subjective psychological wellbeing was associated with sleep difficulties [odds ratio (OR) = 2.39, 95% CI = 1.37–4.18, p = 0.002], higher depression (OR = 6.13, 95% CI = 3.46–10.88, p < 0.001), and anxiety symptoms (OR = 2.95, 95% CI = 1.66–5.22, p < 0.001). In male participants, analysis revealed an association between worse subjective psychological wellbeing and higher depression scores (OR = 9.94, 95% CI = 3.29–30.03, p < 0.001). Conclusion Sex differences are an important factor to consider when evaluating subjective psychological wellbeing. Clinicians should be aware of significant contributors, such as sleep patterns anxiety, and depression, to subjective psychological wellbeing.